Determination of Financial Indicators on Tax Avoidance through Transfer Pricing on Energy Companies - Setyawan, Widyatmanto; Indupurnahayu; Aminda, Renea Shinta (Asian Journal of Management Analytics, 2024)
The main problem of the study is about variables in company size and their effect on tax avoidance. Compared to the results when transfer pricing moderates. The focus of the analysis in this is on company size, receivables, debt, costs, profits against tax avoidance through transfer pricing. The study used quantitative methods with secondary data. Data collection through interview techniques and documentation data collection by recording or collecting data on energy companies listed on the IDX for 2018-2022. From a population of 82 companies, a sample of 52 companies was obtained using purposive sampling according to criteria. The data was tested with panel data regression model data using Chow Test and Hausman Test techniques, and also used E-views application. The results of the study found that financial indicators in energy companies, namely: Company Size, receivables, debts, costs, and profits have a significant positive influence on tax avoidance, and when transfer pricing moderates it has a positive affects the financial performance of energy companies on tax avoidance.